PENGARUH KECERDASAN EMOSIONAL TERHADAP TINGKAT PEMAHAMAN AKUNTANSI DIMODERASI OLEH KEPERCAYAAN DIRT - H. Kirmizi R (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2009)
The purpose of this study is to examine the effect of emotional intelligence in terms of three dimension (self regulation, motivation, and social skills) on the level of understanding of accounting for the students of Accounting Department, Faculty of Economic of State Islamic University Sultan Syarif Kasim Riau. This study also examines the effect of emotional intelligence on the level of understanding of accounting moderated by variable ofstrong self-confidence. This study is an empirical research which is using purposive technic sampling in drawing sample. The craeteria of sample were the students of Accounting Department who have completed 110 semester credit systems by assuming that the students in sample have been completed almost all of the subject presented in eight semesters. Based on the craeteria, sample have been drawn 350 of accounting students. The results of the study are that there has been significant effect of self regulation on the understanding of accounting; there has been a negative effect of strong self-confidence on relationship between motivation and understanding of accounting; therefore, motivation has significantly affected understanding of accounting; and also, there has been negatifeffect of strong self-confidence on relationship between motivation and understanding of accounting; however, social skills could significantly affect understanding of accounting; and finaly, strong self-confidence significantly affect on relationship between social skill and understanding ofaccounting.Keyword: emotional intelligence, self regualtion, motivation, social skills, strong selfconfidence, and level ofunderstanding ofaccounting.